2018
DOI: 10.1002/celc.201801009
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Flower‐Like Co−Mo−S on Reduced Graphene Oxide Composite on Nickel Foam with Enhanced Electrochemical Capacitive Properties

Abstract: Transition metal sulfides have attracted considerable attention due to their excellent electrochemical performance for supercapacitors. Herein, we prepared a Co3S4/CoMo2S4 (Co−Mo−S) composite on reduced graphene oxide/Ni foam (RGO/NF) with unique flower‐like morphology through a carefully time‐controlled sulfurization process. It was found that the vulcanization time has a great influence on the morphology and electrochemical properties of the composites. After 3 hours of vulcanization, the as‐prepared Co3S4/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Figure 3c shows the high‐resolution spectra of Mo 3d. The two main peaks were located at 228.6 and 232.0 eV (229.6 and 232.7 eV in Figure S2c for CMO), which corresponded to Mo 3d 5/2 and Mo 3d 3/2 electron orbitals, respectively, and the peak at 235.3 eV can be ascribed to the existence of Mo 6+ [32,33] . In addition, the small peak near 226.2 eV in CMS/NF‐120 was due to the influence of S 2s photoelectrons.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 3c shows the high‐resolution spectra of Mo 3d. The two main peaks were located at 228.6 and 232.0 eV (229.6 and 232.7 eV in Figure S2c for CMO), which corresponded to Mo 3d 5/2 and Mo 3d 3/2 electron orbitals, respectively, and the peak at 235.3 eV can be ascribed to the existence of Mo 6+ [32,33] . In addition, the small peak near 226.2 eV in CMS/NF‐120 was due to the influence of S 2s photoelectrons.…”
Section: Resultsmentioning
confidence: 95%
“…The two main peaks were located at 228.6 and 232.0 eV (229.6 and 232.7 eV in Figure S2c for CMO), which corresponded to Mo 3d 5/2 and Mo 3d 3/2 electron orbitals, respectively, and the peak at 235.3 eV can be ascribed to the existence of Mo 6 + . [32,33] In addition, the small peak near 226.2 eV in CMS/NF-120 was due to the influence of S 2s photoelectrons. Figure 3d was the S 2p spectrum of CMS/NF-120 phase, the two peaks at 163.0 and 161.4 eV could be attributed to the S 2p 1/2 and S 2p 3/2 electron orbitals of the Mo-S bond, respectively.…”
Section: Chempluschemmentioning
confidence: 99%
“…Mo did not participate. [134,135] Xie et al also synthesized the carbon-based disulfide of vanadium for ion storage. [136] A literature survey revealed that the postmetal sulfides and transition metal sulfides both predicted the same trends, as the enhancement of the electrochemical characteristics of hybrid electrode structures; so, the carbonbased electrode materials may be suitable to solve the drawbacks and problems associated with individual metal sulfides.…”
Section: Three-electrode Measurements Of Individual Metal Sulfidesmentioning
confidence: 99%